People, spaces and places in gendered environments - Demos, Vasilikie; Segal, Marcia Texler (Advances in gender research ;, 2024)
Intersectional in approach, this volume of Advances in Gender Research offers an overview of the ways in which environments - broadly defined to include social, natural and built territories, domains and habitats - are gendered. Rooted in qualitative, feminist and change-oriented perspectives, this international set of scholars and practitioners provides an understanding of how marginalized and indigenous populations, often overlooked, relate to natural and built environments. Drawing on real-world interviews, as well as their political and historical contexts, contributors highlight the voices of women and their interactions with their environments. Chapters critically consider the threats, barriers and limitations of urban design to the movements of women, including those with disabilities, covering cases such as: home-based sex work in Punjab cities workplace environments and their role in women's career building environmental activism and cities Asian American women in STEM disciplines indigenous change agents in the Amazon change in built environments, specifically in Athens and Rome agriculture in the Colombian Amazon queer eco-spirituality Demonstrating how women and other marginalized groups respond to the limits and options imposed by the history and structure of spaces, People, Spaces and Places in Gendered Environments envisions a world beyond colonial, able-bodied, class and patriarchal limitations where freedom of movement functions for all.